Developing soft skills in future foreign language teachers through ICT - Natalia V. Bondar; Tetiana V. Konovalenko (Academy of Cognitive and Natural Sciences, 2024)
Rapidly changing job markets require graduates to possess not only technical skills but also strong soft skills. This study investigates the development of soft skills in future foreign language teachers in Ukrainian universities, focusing on the potential of Information and Communication Technologies (ICT) as a tool. Using action research methods and mixed data collection, we explore (1) the current understanding of soft skills among teachers and students, (2) the perceived importance of different soft skills for future language teachers, (3) existing methods and challenges in soft skills development, and (4) the effectiveness of various ICT tools in promoting soft skills growth. The findings will inform the design of a model for integrating ICT into foreign language teacher education to enhance soft skills development, ultimately contributing to preparing graduates for successful careers in a globalised world.